The Influence of Transformational Leadership, Academic Supervision, and Teachers’ Pedagogical Competence on the Quality of Education: A Quantitative Study in Public Elementary Schools - Sulistyorini, Emmelia Maria; Maryanto, Maryanto; Abdullah, Ghufron (Journal of Educational Sciences, 2025)
The quality of education in public elementary schools is influenced by leadership effectiveness, professional guidance for teachers, and teachers’ competence in managing learning. In East Ungaran District, variations in school performance indicate the need to identify key factors affecting educational quality. This study aims to analyze the influence of the principal’s transformational leadership, academic supervision, and teachers’ pedagogical competence on educational quality. A quantitative approach with a causal survey design was used, involving 148 teachers selected through proportional random sampling. Data were collected using validated and reliable questionnaires and analyzed using multiple linear regression. The findings show that transformational leadership, academic supervision, and pedagogical competence each have a positive and significant effect on educational quality, both partially and simultaneously. Transformational leadership has the strongest influence among the three variables. The coefficient of determination (R²) of 0.562 indicates that 56.2% of the variation in educational quality is explained by these factors. The study concludes that strengthening visionary leadership, systematic supervision, and pedagogical capacity is essential to create a collaborative and sustainable quality-oriented school environment.